Bisexual Stigma, Sexual Violence, and Sexual Health Among Bisexual and Other Plurisexual Women: A Cross-Sectional Survey Study. Issue 9 (22nd November 2019) - Flanders, Corey E.; Anderson, RaeAnn E.; Tarasoff, Lesley A.; Robinson, Margaret
Abstract : Bisexual women experience higher rates of sexual victimization relative to heterosexual and lesbian women, and worse sexual health outcomes. Though these health disparities are well documented in the literature, few empirical data have been published on what factors are driving these disparities. Further, research documenting sexual victimization and health of plurisexual (i.e., attracted to more than one gender) women group all participants as bisexual. We do not know whether these experiences are similar across subgroups of plurisexual women. The current study reports on data from a cross-sectional survey, analyzing the relationships between bisexual-specific stigma and sexual violence, as well as other sexual health outcomes, across a sexually diverse group of plurisexual participants. Findings indicate that bisexual stigma is a significant predictor of lifetime sexual violence (odds ratio [OR] = 1.99:, p = .015) and verbal coercion (OR = 2.60, p = .004), but not other outcomes. There are differences across sexual identity categories, with bisexual participants being less likely to report sexual violence and verbal coercion, and less likely to access sexually transmitted infection/human immunodeficiency syndrome testing, compared to other plurisexual groups. Our findings support that bisexual stigma is an important factor to consider in understanding sexual violence disparities experienced by bisexual and other plurisexual women.